Therapeutic perspective of light for coronavirus treatment (Research, Society and Development, 2020)
We are currently facing a pandemic that continuously causes high rates of deaths and catastrophic and countless economic and psychosocial consequences. Thus, this period requires a quick search for viable procedures that can allow us to use safe and non-invasive clinical tools as prophylactic or even adjuvant methods in the treatment of COVID-19, thus constituting an important challenge to the medical clinic. Scientific reports show that in 1918 the impacts of “Spanish influenza” were reduced significantly after treatment with light, phototherapy. Thus, the objective of this study is to analyze, through a theoretical study of reflective analysis, the impacts of phototherapy on pandemic and similar infections caused by coronavirus. Evidence shows that phototherapy using mainly light lasers and light-emitting diodes (LEDs) at the blue wavelength has a potential antimicrobial effect, just as red and near-infrared wavelengths have been shown to attenuate lung diseases and reduce respiratory disorders similar to complications associated with coronavirus infections. Thus, it is suggested, for the health sector, the inclusion of light technologies, of low cost and readily available within the arsenal of therapeutic resources, for patients with infections, including coronavirus by COVID-19.